Does mutual fund family size matter? International evidence - Miguel, A. F. (2021)
We use data from 33 countries to study how a fund’s affiliation with large families shapes the flow–performance relationship internationally. Our results show that the effect of family size on the fund flows’ response to performance depends on the sophistication of investors in a country. While less sophisticated investors are persuaded by the great visibility and strategies of funds that are affiliated with large and established families, more sophisticated investors are not. Affiliation with a large family increases the convexity of the flow–performance relationship in countries where investors are less sophisticated but decreases this convexity in countries with more sophisticated investors. These results are important for investors, mutual fund companies and regulators because the flow–performance sensitivity determines the assets under management, the level of fees, risk-taking, and the performance of the fund.